TEMPORAL SEIZURE OF AN OBJECT OF A MISDEMEANOR (Heritage, 2024)
Under the Law on Misdemeanors there is proscribed a possibility of a temporal seizure of certain objects from a misdemeanor offender. The temporal seizure can be imposed by the court or other relevant state organs. Those items could be permanently taken away if the court impose a safeguard measure of seizure of objects. It is has been recently defined that in the Republic of Serbia there is an obligation of seizure of vehicle from the offenders of grave misdemeanors. The subject of this paper is related to the temporary seizure of items. Author primarily conducts a critical analysis of the Law on Misdemeanors provisions, as well as other laws and regulations that contain provisions regulating the temporary seizure of items. One of the author’s aims is to emphasize certain illogicalities in reference to a misdemeanor offender of a milder punitive act (misdemeanor), and also harsh consequences that appear on behalf of a person from which the items are taken away.
Keywords: misdemeanor, criminal act, traffic, seizure of an item, safeguard measure